Expression map of the human exome in CD34+ cells and blood cells: increased alternative splicing in cell motility and immune response genes. - Sylvie Tondeur (Public Library of Science (PLoS), 2010)
Background Hematopoietic cells are endowed with very specific biological functions, including cell motility and immune response. These specific functions are dramatically altered during hematopoietic cell differentiation, whereby undifferentiated hematopoietic stem and progenitor cells (HSPC) residing in bone marrow differentiate into platelets, red blood cells and immune cells that exit into the blood stream and eventually move into lymphoid organs or inflamed tissues. The contribution of alternative splicing (AS) to these functions has long been minimized due to incomplete knowledge on AS events in hematopoietic cells. Principal findings Using Human Exon ST 1.0 microarrays, the entire exome expression profile of immature CD34+ HSPC and mature whole blood cells was mapped, compared to a collection of solid tissues and made freely available as an online exome expression atlas (Amazonia Exon! : http://amazonia.transcriptome.eu/exon.php). At a whole transcript level, HSPC strongly expressed EREG and the pluripotency marker DPPA4. Using a differential splicing index scheme (dsi), a list of 849 transcripts differentially expressed between hematopoietic cells and solid tissues was computed, that included NEDD9 and CD74. Some of these genes also underwent alternative splicing events during hematopoietic differentiation, such as INPP4B, PTPLA or COMMD6, with varied contribution of CD3+ T cells, CD19+ B cells, CD14+ or CD15+ myelomonocytic populations. Strikingly, these genes were significantly enriched for genes involved in cell motility, cell adhesion, response to wounding and immune processes. Conclusion The relevance and the precision provided by this exon expression map highlights the contribution of alternative splicing to key feature of blood cells differentiation and function.